Evaluating efficacy and safety of sub-anesthetic dose esketamine as an adjuvant to propofol/remifentanil analgosedation and spontaneous respiration for children flexible fibreoptic bronchoscopy: a prospective, double-blinded, randomized, and placebo-controlled clinical trial - Zhong, Yu; Jiang, Min; Wang, Yunshi; Su, Tingting; Lv, Yuanzhi; Fan, Zhiqing; Ning, Hengyi; Yang, Yilan; Chen, Yanhua; Xie, Yubo (Frontiers in Pharmacology, 2023)
Background: Flexible fiberoptic bronchoscopy (FFB) for children is widely performed under sedation. Currently, the optimal sedation regimen remains unclear. Esketamine is an N-methyl-D-aspartic acid (NMDA) receptor antagonist, which has stronger sedative and analgesic effects and exerts less cardiorespiratory depression than other sedatives. The purpose of this study was to evaluate whether a subanesthetic dose of esketamine as an adjuvant to propofol/remifentanil and spontaneous ventilation compared with control reduces the procedural and anesthesia-related complications of FFB in children. Materials and methods: Seventy-two children ≤ 12 years of age who were scheduled for FFB were randomly assigned, in a 1:1 ratio, to the esketamine-propofol/remifentanil (Group S, n = 36) or to the propofol/remifentanil group (Group C, n = 36). All children were retained spontaneous ventilation. The primary outcome was the incidence of oxygen desaturation (respiratory depression). Perioperative hemodynamic variables, blood oxygen saturation (SPO2), end-tidal partial pressure of carbon dioxide (PetCO2), respiratory rate (R), and the Bispectral index (BIS), induction time, procedural time, recovery time, the time to the ward from the recovery room, consumption of propofol and remifentanil during the procedure and the appearance of adverse events, including paradoxical agitation following midazolam administration, injection pain, laryngospasm, bronchospasm, PONV, vertigo, and hallucination were also compared. Results: The incidence of oxygen desaturation was significantly lower in Group S (8.3%) compared to Group C (36.1%, p = 0.005). The perioperative hemodynamic profile including SBP, DBP, and HR were more stable in Group S than that in Group C (p < 0.05). Consumption of propofol and remifentanil was lower in Group S than in Group C (p < 0.05). Furthermore, PAED scores, cough scores and injection pain were lower in the Group S than in Group C (p < 0.05). The recovery time of Group S was slightly longer than that of Group C (p < 0.05). Nobody happened paradoxical agitation following midazolam administration, PONV, vertigo, and hallucinations in both groups (p > 0.05). Conclusion: Our findings indicate that a subanesthetic dose of esketamine as an adjuvant to propofol/remifentanil and spontaneous respiration is an effective regimen for children undergoing FFB. Our findings will provide a reference for clinical sedation practice during these procedures in children. Clinical Trail Registration: Chinese clinicaltrials.gov registry (identifier: ChiCTR2100053302).